Human trafficking : exploring the international nature, concerns, and complexities - Winterdyk, John; Perrin, Benjamin; Reichel, Philip L. (CRC Press, 2012)
Introduction; John Winterdyk, Benjamin Perrin, and Philip ReichelDefining Human Trafficking and Its Nuances in a Cultural Context; Cindy J. Smith and Kristiina KangaspuntaData on Human Trafficking: Challenges and Policy Context; Jo GoodeyExplaining Human Trafficking; Julie Kaye and John WinterdykVoices from Victims and Survivors of Human Trafficking; Claude D'EstréeCrime Control versus Social Work Approaches in the Context of the ""3P"" Paradigm: Prevention, Protection, Prosecution; Karin Bruckmüller and Stefan SchumannHuman Trafficking and Police Investigations; Annette HerzProsecution of Tra.